Clusters explaining the relation between menopause and self-reported periodontal disease: a cross-sectional study - Hani T. Fadel; Lujain A. Qarah; Manal O. Alharbi; Alla Al-Sharif; Doaa S. Al-Harkan; Saba Kassim; Osama Abu-Hammad; Najla Dar-Odeh (PeerJ)
Background Menopause is an important milestone in the women’s life continuum and is associated with potentially adverse effects, including those related to oral health. This study assessed self-reported periodontal disease in relation to menopausal status. Methods A cross-sectional study involving a convenience sample of female university dental hospital attendees was conducted using a validated, self-administered, self-reported periodontal disease questionnaire. A two-step cluster analysis was used to categorize the participants based on menstrual period (MP) continuity, systemic diseases and age. Differences between clusters were analyzed using chi-square test. Results From 112 included participants, three clusters resulted from the analysis: Cluster #1 (37 ± 8 years, no systemic diseases and continued MP), Cluster #2 (40 ± 10, with systemic diseases and continued MP) and Cluster #3 (54 ± 9, with systemic diseases and discontinued MP). Cluster #3 tended to have less optimal oral hygiene habits and more missing teeth (p > 0.05). Clusters #1 and #2 insignificantly reported more gingival bleeding, tooth sensitivity and calculus (p > 0.05). Cluster #3, on the other hand, presented with more self-reported oral dryness (p ≤ 0.05). Conclusions Within study limits, clusters of menopausal women with systemic diseases reported high symptoms of periodontal disease that were not significantly different from younger individuals, with the exception of oral dryness.